Penerapan Metode Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) Dalam Pemilihan Kepala Laboratorium Menggunakan Pembobotan Rank Order Centroid (ROC) - Puspa Ayu Sholeha; Rima Tamara Aldisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In selecting the head of the laboratory, someone who has extensive knowledge in the specific field of the laboratory is needed, as well as good management and leadership skills. They may also be involved in developing new methods, selecting equipment, and developing laboratory policies. However, the challenge in the selection process for a new laboratory head is the high number of applicants and a series of selection stages which are time-consuming, including administrative selection, competency evaluation, and interviews. This causes difficulties for schools in making decisions to get candidates for laboratory heads that match their expectations. In solving problems in laboratory selection, the authors make 5 criteria including qualifications, experience, leadership, communication skills, and responsibility. So this research also needs a system that can help to solve existing problems. A system that can help solve problems is a Decision Support System (SPK). In completing this research, the writer has to find the weight value of the criterion data where the writer uses the ROC method to produce the weight value and after that the writer also searches for the ranking value using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The produce of ranking values in the TOPSIS method, the author must work according to predetermined steps in order to obtain precise and accurate preference values. The ROC and TOPSIS methods really help the writer in generating values accurately. So from the above calculations using the TOPSIS method the chosen head of the laboratory is Zakiyah Alifah with a total value of 1.